Determination of the optimum platelet-rich plasma method for the essential amount of platelets (Annals of Medical Research, 2023)
Aim: Platelet-rich plasma (PRP) is the cellular plasma component containing a higher platelet concentration obtained by centrifugation of autologous peripheral blood. PRP has an auxiliary role in regenerative medicine treatment. Current treatment protocols for tissue repair strategies may be globally insufficient. PRP treatment via Platelet-released growth factors (GF) supports inflammation, proliferation, and wound healing. PRP studies have progressed and have proposed different formulations in recent years. Although various methods and devices are used, there are few and different standardized protocols to obtain PRP with the highest platelet concentration. Although anticoagulants containing citrate are primarily preferred in PRP production To provide effective platelet concentration in PRP, we noticed differences in the literature regarding PRP tube volumes, anticoagulant-citrate, and blood amounts. We aimed to obtain the most appropriate platelet concentration in PRP treatment by using different concentration ratios of Acid Citrate dextrose (ACD) solution A and different blood amounts and introducing a new treatment method to the literature.Materials and Methods: The blood of 30 individuals aged between 30 and 75 was taken into 10cc laboratory tubes, and 15cc and 18cc hourglass-shaped PRP tubes containing 8% ACD-solution A. Blood fractions were separated by centrifugation, buffy coat area was collected, and count platelet amount by Hematology Analyzer.Results: The platelet amount per µl was statistically significantly higher in 18cc blood compared to 15cc and 10cc. Platelet amounts obtained from 15 and 18cc peripheral blood with 8% ACD-solution A were above the effective treatment amount recommended in the literature.Conclusion:  It was observed that the amount of used blood volume was correlated with the amount of obtained platelets.
Keywords: Platelet-rich plasma (PRP); Acid citrate dextrose (ACD); Autologous peripheral blood; Platelet